The Influence of Anode Inner Contour on Atmospheric DC Plasma Spraying Process - Kui Wen; Min Liu; Kesong Zhou; Xuezhang Liu; Renzhong Huang; Jie Mao; Kun Yang; Xiaofeng Zhang; Chunming Deng; Changguang Deng (Advances in Materials Science and Engineering)
In thermal plasma spraying process, anode nozzle is one of the most important components of plasma torch. Its inner contour controls the characteristics of plasma arc/jet, determining the motion and heating behaviors of the in-flight particles and hence influencing the coating quality. In this study, the effects of anode inner contour, standard cylindrical nozzle, and cone-shaped Laval nozzle with conical shape diverging exit (CSL nozzle) on the arc voltage, net power, thermal efficiency, plasma jet characteristics, in-flight particle behaviors, and coating properties have been systematically investigated under atmospheric plasma spraying conditions. The results show that the cylindrical nozzle has a higher arc voltage, net power, and thermal efficiency, as well as the higher plasma temperature and velocity at the torch exit, while the CSL nozzle has a higher measured temperature of plasma jet. The variation trends of the plasma jet characteristics for the two nozzles are comparable under various spraying parameters. The in-flight particle with smaller velocity of CSL nozzle has a higher measured temperature and melting fraction. As a result, the coating density and adhesive strength of CSL nozzle are lower than those of cylindrical nozzle, but the deposition efficiency is greatly improved.